A novel sine wave based UWB pulse generator design for single/multi-user systems - Mohammed, Ahmed R.; Al-Khateeb, Khalid A. Saeed; Islam, Md Rafiqul (Maxwell Scientific Organization, 2012)
In this study, a novel Ultra Wideband (UWB) pulse generator design for single- and multi-user systems is presented. The proposed pulse generator is based on new simple and effective design to generate the UWB pulses through sine wave shaping. For single-user systems, three models for the proposed pulse generator working with Frequency Modulation (FM), Bi-Phase Modulation (BPM) and On-Off Keying (OOK) are introduced. The first generator model has 250 Mbps throughput from a 250 MHz sine wave oscillator, while the second model works on 500 Mbps. The third model for three separate users for multiuser systems using Frequency Division Multiple Access (FDMA), while the same model can be configured to work for a single-user with 750 Mbps using Multiple Input Multiple Output (MIMO) technique. The generated pulse is compatible with the Federal Communication Commission (FCC) regulations of UWB indoor emission mask. A lumped low pass filter has been designed to achieve the sine wave shaping. The simulation results verify the proposed design and its effectiveness of using sine wave shaping for UWB pulse generators.